Cigarette taxes and the social market - Benjamin Hansen; Joseph J. Sabia; Daniel I. Rees (Institute for the Study of Labor (IZA), 2011)
Previous researchers have argued that the social market for cigarettes insulates its participants from policies designed to curb youth smoking. Using state Youth Risk Behavior Survey data, we examine whether recent changes in state cigarette taxes affected how young smokers obtained their cigarettes. Our estimates suggest that tax increases reduce youth smoking participation primarily through their effect on third-party purchase, although there is evidence that they are negatively related to borrowing among younger teenagers and negatively related to direct purchase among older teenagers.
urn:nbn:de:101:1-201104134029
Keywords: I10; I12; 330; youth smoking; cigarette taxes; Tabaksteuer; Wirkungsanalyse; Jugendliche; Rauchen; Soziale Beziehungen; USA